Ethnography : principles in practice - Hammersley, Martyn; Atkinson, Paul, 1947- (Abingdon, Oxon : Routledge, 2019)
Now in its fourth edition, this leading introduction to ethnography has been thoroughly updated and substantially rewritten. The volume offers a systematic introduction to ethnographic principles and practice, and includes a new chapter on 'Ethnography in the digital world'. The authors argue that ethnography is best understood as a reflexive process. This requires recognition that social research is part of the world that it studies, and demands that researchers reflect on how they shape both data and analysis. Starting in Chapter1 with an outline of the principle of reflexivity, against the background of competing research philosophies, the authors go on to discuss the main features of ethnographic work, including: the selection and sampling of cases the problem of access field relations and observation interviewing the use of documents recording and organizing data the process of data analysis and writing research reports. There is also consideration of the ethical issues involved in ethnographic research. Throughout, the discussion draws on a wide range of illustrative material from classic and more recent studies, within a global context. The new edition of this popular textbook will be an indispensable resource for undergraduate and postgraduate students, and for all researchersusing ethnographic methods in the social sciences and the humanities.
Progressive focusing: problems, descriptions, explanations, theoryAn emphasis on action; Generating ideas and 'coding the data'; Constant comparative method: developing the central categories; Developing typologies and models; Theories and the comparative method; Types of theory; Concepts and indicators; 'Respondent validation' or 'member checking'; Triangulation; Conclusion; Chapter 10: Writing ethnography; Chapter 11: Ethics; Informed consent; Consequences for future research; The issue of ethical regulation; Conclusion; Epilogue: a distinctive analytic sensibility; Conclusion; References
OCLC-licensed vendor bibliographic record.
Keywords: Ethnology -- Methodology; Ethnology -- Fieldwork; Social sciences -- Fieldwork; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; SOCIAL SCIENCE / Customs & Traditions; SOCIAL SCIENCE / Sociology / General